Debt and productivity: Evidence from firm-level data - Roger M. Gomis; Sameer Khatiwada (Graduate Institute of International and Development Studies, 2017)
There are relatively few studies that use micro data to shed light on the relationship between finance and economic growth - the few that exists show that there is a positive relationship between debt and future productivity growth. Meanwhile, several new macro-econometric studies have shown that there is a threshold of financial development above which finance negatively impacts growth - our paper contributes to this literature by examining whether this finding holds when we examine firm level data. Our data covers over 100 countries, both advanced and developing & emerging and spans close to 30 years (1986-2014). Our preliminary results are the following: i) firm level leverage is positively associated with productivity; ii) the strength of this association declines in employment of the firm; iii) there is diminishing returns to leverage in terms of its impact on productivity but we don't see a threshold beyond which the returns drop; iv) aggregate leverage in a country has a negative effect on firm productivity, controlling for strength of institutions and level of economic and financial development in the country. Furthermore, given the potential issue of endogeneity, we examine the impact of leverage on expected and unexpected components of productivity - our results show that leverage is positively associated with the unexpected component of firm productivity, thus providing evidence against reverse causality.
Keywords: D24; G21; G30; O16; O40; 330; total factor productivity (TFP); debt; finance and growth